2022
DOI: 10.1111/apt.17104
|View full text |Cite
|
Sign up to set email alerts
|

Rectal hyposensitivity: a common pathophysiological finding in patients with constipation and associated hypermobile Ehlers–Danlos syndrome

Abstract: Background and Aims: To evaluate symptom presentation and underlying pathophysiology of colonic/anorectal dysfunction in females with functional constipation (FC) and hypermobile Ehlers-Danlos syndrome (hEDS)/hypermobility spectrum disorder (HSD) Methods: Case-control study of 67 consecutive female patients with an established diagnosis of hEDS/HSD referred to a specialist centre for investigation of FC (Rome III criteria), age-matched (1:2 ratio) to 134 female controls with FC scoring 0 on the validated 5-poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…These results were consistent with findings from previous studies [17]. Using 2 abnormal sensory levels, based on the published normal values [10] for the diagnosis of rectal hyposensitivity we showed that nearly 40% of hEDS/HSD patients had rectal hyposensitivity which is comparable to the data from Choudhary et al [18]. The rate of rectal hyposensitivity in the non hEDS/HSD group was also high at 36% which is likely to be related to the characteristics of patients population in our cohort [19].…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with findings from previous studies [17]. Using 2 abnormal sensory levels, based on the published normal values [10] for the diagnosis of rectal hyposensitivity we showed that nearly 40% of hEDS/HSD patients had rectal hyposensitivity which is comparable to the data from Choudhary et al [18]. The rate of rectal hyposensitivity in the non hEDS/HSD group was also high at 36% which is likely to be related to the characteristics of patients population in our cohort [19].…”
Section: Discussionsupporting
confidence: 92%
“…Chaudhary et al have presented an ambitious case-control study in constipated women with or without a hEDS/ HSD diagnosis comparing gastrointestinal (GI) symptoms and the outcome of GI physiology tests. 2 The patients with hEDS/HSD reported higher scores on constipation symptoms, and rectal hyposensitivity was twice as common when measured by a volume-controlled anorectal manometry balloon. As pointed out by the authors, the latter might be a relevant factor for considering biofeedback treatment, but there are further study implications to highlight, both from a clinical and scientific point of view.Focusing on the GI symptoms, 91% and 82%, respectively, of patients with hEDS/HSD and controls reported abdominal pain "≥ sometimes" as assessed by the Cleveland constipation score.…”
mentioning
confidence: 88%
“…The pathophysiologic link between hEDS/HSD and the DGBI is obscure and it is not known if specific treatment considerations are warranted when there is a co‐occurrence of the diagnostic groups. Chaudhary et al have presented an ambitious case–control study in constipated women with or without a hEDS/HSD diagnosis comparing gastrointestinal (GI) symptoms and the outcome of GI physiology tests 2 . The patients with hEDS/HSD reported higher scores on constipation symptoms, and rectal hyposensitivity was twice as common when measured by a volume‐controlled anorectal manometry balloon.…”
mentioning
confidence: 99%
“…We thank Dr. Törnblom for his summary of our study and for his interpretation of our salient findings 1,2 . We would like to address some of his points.…”
mentioning
confidence: 89%
“…8 Finally, while we agree that the high prevalence of opioid use in patients with hEDS/HSD is worrying, we are satisfied that this is not confounding our findings 9 as described by the statistical adjustments in our paper. 2 However, we appreciate that the high prevalence of opioid use may be increasing the risk of narcotic bowel syndrome, and exacerbating constipation and abdominal pain, making it harder to manage these symptoms. Opioid withdrawal would be an important component of management as outlined in a recent publication that provides guidance for managing gastrointestinal symptoms in patients with hEDS/HSD.…”
mentioning
confidence: 99%